Penggunaan Big Data Dalam Meningkatkan Pelayanan Publik E-Ktp Di Dinas Kependudukan Dan Pencatatan Sipil Kota Sorong - Hasrianti, Hasrianti; Lestari, Ana; Salmah, Ummu; Rusdi, Rusdi (Universitas Muhammadiyah Sorong, 2023)
This research aims to determine the implementation and benefits of using Big Data in e-KTP public services in the Sorong City Dukcapil Office as well as the potential for further development and improvement of the e-KTP public service system using Big Data. The research method used is qualitative with data collection techniques through observation, interviews and documentation. Data analysis includes data reduction, data presentation, and drawing conclusions, with data validity maintained through credibility tests. The research results show that the use of Big Data has increased efficiency in e-KTP services with a faster and more efficient processing process. Centralized and well-integrated e-KTP data has resulted in high data accuracy. Cross-sector collaboration has enabled the exchange of necessary information and increased data accuracy. Big Data analysis helps understand population profiles and service needs,and improves access to services. The use of Big Data also provides significant benefits for governments, including administrative efficiency, data-based decision making, and resource optimization.